Age-Related Differences in the Cognitive, Visual, and Temporal Demands of In-Vehicle Information Systems - Cooper, Joel M.; Wheatley, Camille L.; McCarty, Madeleine M.; Motzkus, Conner J.; Lopes, Clara L.; Erickson, Gus G.; Baucom, Brian R. W.; Horrey, William J.; Strayer, David L. (Frontiers in Psychology, 2020)
In-vehicle information systems (IVIS) refer to a collection of features in vehicles that allow motorists to complete tasks (often unrelated to driving) while operating the vehicle. These systems may interfere, to a greater extent, with older drivers’ ability to attend to the visual and cognitive demands of the driving environment. The current study sought to examine age-related differences in the visual, cognitive and temporal demands associated with IVIS interactions. Older and younger drivers completed a set of common tasks using the IVIS of six different vehicles while they drove along a low-density residential street. Evaluation measures included a Detection Response Task (DRT), to assess both cognitive and visual attention, subjective measures following each condition using the NASA Task Load Index (TLX), and video footage of the driving environment during data collection. Two age cohorts were evaluated: younger drivers between 21-36 years of age, and older drivers between 55-75 years of age. Participants completed experimental tasks involving interactions with the IVIS to achieve a specific goal (i.e., using the touch screen to tune the radio to a station; using voice commands to find a specified navigation destination, etc.). Performance of tasks varied according to different Modes of Interaction available in the vehicles. In general, older drivers took longer to complete tasks, were slower to react to stimuli, and reported higher task demand when interacting with IVIS. Older drivers stand to benefit the most from advancements in-vehicle technology, but ironically may struggle the most to use them. The results of this study suggest significant age-related costs in the distraction potential of IVIS on the road.